Seasonal expression patterns of clock-associated genes in the blue mussel Mytilus edulis. (21st October 2017) - Chapman, Emma C.; O'Dell, Alasdair R.; Meligi, Noha M.; Parsons, Daniel R.; Rotchell, Jeanette M.
ABSTRACT: Environmental cues allow organisms to synchronise their internal biological rhythms with external environmental cycles. These rhythms are regulated on a molecular level by oscillating interactions between clock genes and their proteins. Light is a particularly relevant environmental cue, provisioning daily information via light/dark cycles as well as seasonal information via day-length (photoperiod). Despite the ecological and commercial importance of bivalves, little is known about the interactions comprising their molecular clock mechanism. This study investigates the link between the annual seasonal progression and reproductive development in the blue mussel ( Mytilus edulis ), using mRNA expression patterns of clock-associated genes: Clock, Cry1 ¸ ARNT, Timeout -like, ROR/HR3 and aaNAT, in the gonads of both sexes, sampled over three daily time-points on a tidal beach during the winter and summer solstices. Significant differences in mRNA expression levels, including some seasonal differences at comparable time-points, were detected for all genes with the exception of Timeout -like. These differences occurred seasonally within sex ( Clock, Cry1, ROR/HR3 ), seasonally between sexes ( Clock, Cry1, ARNT, ROR/HR3, aaNAT ) and daily between sexes ( Cry1 ), although no significant daily differences were detected in summer or winter for either sex for any of the genes. This study reveals that clock-associated genes show seasonal responses in this species of bivalve. Understanding the mechanisms by which environmental cues drive biological rhythms is critical to understanding the seasonal sensitivity of this keystone species to environmental changes.